Pelatihan Aplikasi e-IM3 Edu Pada Penyandang Disabilitas untuk Meningkatkan Kualitas Produksi Batik Ciprat Langitan - Endang Sri Maruti; Wasilatul Murtafiah; Rischa Pramudia Trisnani; Sylfi Anjarwati; Meila Annisa Putri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
This community service activity aims to improve the skills of people with disabilities in the Batik Ciprat Langitan community in utilizing digital technology through the e-IM3 edu application. Situational analysis shows that the group of people with disabilities who are members of the Sheltered Workshop Peduli Sambung Roso already have good batik skills but are hampered in production management, recording work results, and online product marketing. The activity methods include socialization, application usage training, practical assistance, and evaluation of digital skill improvement. After receiving e-IM3 edu training, which includes the concept of color mixing and the decision-making system regarding which colors to use for batik production, the activity results show an 80% increase in participants' digital skills and an increase in the quality of production and marketing of ciprat batik products. People with disabilities who initially only mixed basic colors in inconsistent measurements or by estimation, became more careful and consistent so that the resulting color in one production run can be consistent. This training has a positive impact on the economic independence of people with disabilities and strengthens the model of inclusive technology-based social enterprises.